Thermodynamic re-optimization of the Cu-Mg-Sn system at the Cu-Mg side - Miettinen J.; Vassilev G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Thermodynamic description of the ternary Cu-Mg-Sn system at its Cu-Mg side is presented. The thermodynamic parameters of the binary sub-systems, Cu-Mg, Cu-Sn and Mg-Sn, are taken from the earlier SGTE-based assessments (modifying the Mg-Sn description slightly) and those of the Cu-Mg-Si system are optimized in this study using the experimental thermodynamic and phase equilibrium data. The solution phases of the systems are described with the substitutional solution model and the intermetallic Cu2Mg compound (Laves C15), treated as simple semi-stoichiometric phases of the (A,B)pCq type, is described with the twosublattice model. The present ternary description is valid for tin contents up to 45 wt% (xSn≈0.30).